PERSEPSI AUDITOR BKM DENGAN PEMAKAI LAPORAN KEUANGAN BKM TENTANG EXPECTATION GAP DALAM HAL INDEPENDENSI, KOMPETENSI AUDITOR, PERAN DAN TANGGUNG JAWAB AUDITOR - Fakhrial Firdausy Alhaq (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research purpose  to examine whether or not there’s a significant difference in perceptions between Auditor BKM with  financial statement users in terms of independence, auditor competency, role and responsibilities of auditors. Methods used  in this research is form of  survey methods.  Sampling was  done using purposive sampling technique. The data used  in this research is form of primary data  through a survey  questionnaire that  was  distributed  directly  to the respondents.  Perceptions of respondents measured  from  the answers  to  the questions  in the questionnaire  using  an  interval  size from Likert scale. Validity tests using the  Pearson  Product Moment  Correlation.  Reliability tests  using Cronbach's Alpha technique and Normality tests using Kolmogorov Smirnov One-Sample Test. To test the hypothesis using Independent sample t-test. Based on the results of hypothesis testing showed that the expectation gap between auditors of BKM  with financial statement users in terms of independence,  auditor competency,  role and  responsibilities of  auditors.  Auditor  BKM  have a higher perception in terms of independence, Auditor Competency, Role and Responsibilities of Auditors compared to financial statement users of BKM. Keywords:  expectation  gap,  perception,  auditors,  financial statement users,  independence, auditor competencies, role and responsibilities of auditor.